2006
DOI: 10.1051/hydro:2006007
|View full text |Cite
|
Sign up to set email alerts
|

Chercheurs d'or et contamination par le mercure des systèmes aquatiques continentaux de Guyane – Risques à l'égard des populations humaines

Abstract: Résumé -La pollution par le mercure en Amazonie brésilienne et en Guyane française est principalement liée aux activités d'orpaillage, qui rejettent des quantités importantes de mercure élémentaire (Hg • ) lors des étapes d'amalgamation et amplifient les apports de Hg inorganique (HgII) via l'érosion des sols et des sédiments, naturellement riches en métal. Dans le cadre du programme de recherche interdisciplinaire « Mercure en Guyane », initié en 1997 par le CNRS/PEVS, une étude approfondie a été menée sur la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Beyond the nutritional aspects, food is also associated with the serious hazards of heavy metals such as mercury and lead. Given the importance of illegal gold mining, mercury pollution and concentration by predatory fish is a significant problem with autochthonous populations who often rely on fishing (31)(32)(33)(34)(35)(36)(37)(38). There again, the first 1,000 days after conception is a period of particular vulnerability, and some studies in French Guiana identified specific neurological and neuropsychological deficits in Amerindian children that were consistent with known targets of mercury neurotoxicity (34).…”
Section: Specific External Exposuresmentioning
confidence: 99%
“…Beyond the nutritional aspects, food is also associated with the serious hazards of heavy metals such as mercury and lead. Given the importance of illegal gold mining, mercury pollution and concentration by predatory fish is a significant problem with autochthonous populations who often rely on fishing (31)(32)(33)(34)(35)(36)(37)(38). There again, the first 1,000 days after conception is a period of particular vulnerability, and some studies in French Guiana identified specific neurological and neuropsychological deficits in Amerindian children that were consistent with known targets of mercury neurotoxicity (34).…”
Section: Specific External Exposuresmentioning
confidence: 99%
“…Here, we measured the concentrations of Hg found in different types of phytotelmata (hereafter referred to as "pools") over six different locations in French Guiana, a French Overseas Territory with high prevalence of ASGM (Boudou et al 2006;Grimaldi et al 2015).…”
Section: Introductionmentioning
confidence: 99%